Effects of salivary pH on coating durability of two different aesthetic archwire coatings under a simulated intraoral environment - Youssef Chikh Abdulkader; Anis F. Kamaruddin; Rabiatul Basria S.M.N. Mydin (Elsevier, 2020)
Objectives: This study compared the effects of normal salivary pH, and acidic pH found in patients with poor oral hygiene, on the durability of aesthetic archwire coated with epoxy resin and polytetrafluoroethylene (PTFE). Methods: The posterior parts of the archwires were sectioned into 20 mm segments (N = 102) and divided among six groups. Four groups were treated with different pH levels and two served as controls. The specimens were immersed in individual test tubes containing 10 ml of artificial saliva adjusted to a pH of 6.75 or 3.5. The tubes were sealed and stored in a 37 °C water bath for 28 days. After 28 days, the specimens were ligated to brackets embedded in an acrylic block and subjected to mechanical stress using an electronic toothbrush for 210 s. The specimens were photographed, and images were measured for coating loss using AutoCAD® software. Surface morphology was observed using a scanning electron microscope (SEM). Results: Significant coating loss (p < 0.001) was found in the epoxy resin groups, regardless of pH value, but not in the PTFE groups. The acidic pH caused epoxy resin layer coating loss by twice as much as normal pH. SEM revealed existing manufacturing defects on the as-received epoxy resin coating, whereas the retrieved epoxy resin demonstrated rupture, roughness, and coating loss in multiple locations. Significance: Epoxy resin coatings demonstrate poor durability in acidic environments. This condition is worsened by the existing manufacturing defects found on as-received archwires. Hence, archwires coated with epoxy resin are not recommended in patients with poor oral hygiene.